BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
Aphelenchida, Longidoridae and Trichodoridae- Their Systematics and Bionomics. Author: D.J. Hunt, Published by : CAB International, Wallingford, Oxon OXlO 8DE, UK, 1993, 352 pp. Â